2017
DOI: 10.3141/2661-09
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Behaviors and Habits of Distracted College Pedestrians While Walking

Abstract: Walking requires paying attention to the surrounding environment to ensure safe maneuvers. Walkers engaging in multitask activities such as texting, calling, listening to music, snacking, and reading while walking have detrimental effects on safety similar to those experienced with distracted drivers. Because this is an emerging problem, few data have been collected to assess the negative impact of distracted walking on safety. The present survey was conducted to collect information on distracted walking by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…A slower walking speed coupled with a more cautious gait has been associated with a more precarious balance (Nymark et al, 2005). Moreover, distracted walking also reduces our information processing capacity as a result of the elevated cognitive, manual, and visual workloads of performing multiple tasks simultaneously (walking and smartphone operations; White et al, 2017). Therefore, the combination of the factors aforementioned could result in considerable injury propensities while walking in complex and dynamic environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A slower walking speed coupled with a more cautious gait has been associated with a more precarious balance (Nymark et al, 2005). Moreover, distracted walking also reduces our information processing capacity as a result of the elevated cognitive, manual, and visual workloads of performing multiple tasks simultaneously (walking and smartphone operations; White et al, 2017). Therefore, the combination of the factors aforementioned could result in considerable injury propensities while walking in complex and dynamic environments.…”
Section: Discussionmentioning
confidence: 99%
“…Our perception and attention have a limit (Shapiro, 2001). Distractions that divert an individual's attention away from their primary task and toward a secondary one can affect how well the primary task is completed (White et al, 2017). Likewise, it is believed that the use of smartphones impacts pedestrians' performance of the primary task-walking-by increasing their cognitive (Nasar et al, 2008), motor (Lin & Huang, 2017), and visual workloads (Lim et al, 2015;Lin & Huang, 2017) as well as reducing their ability to perceive the environment.…”
mentioning
confidence: 99%
“…Most of the previous studies have focused on situation awareness reduction and related risk of collision injuries. Moreover, the distraction caused by smartphone operation can also affect human locomotion and gait performance and subsequently increase the risk of falling (White et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With advancements in communication technology and the rise in popularity of mobile phones, mobile phones have become an integral part of contemporary life. Several observational studies (7)(8)(9)(10)(11)(12)(13) and questionnaire surveys (14)(15)(16)(17) have indicated that mobile phone use by pedestrians is widespread.…”
mentioning
confidence: 99%
“…Distracted walking is linked to slower walking speeds (18)(19)(20)(21)(22)(23)(24), a smaller perceptual visual field (25,26), longer response times (27,28), less awareness of the surroundings (29)(30)(31)(32)(33), and a lower capacity for cognitive processing (34,35). Furthermore, walking while distracted may increase the likelihood of engaging in unsafe walking behaviors (36)(37)(38)(39)(40)(41)(42) and the probability of being involved in a traffic collision (17,(43)(44)(45)(46).…”
mentioning
confidence: 99%